THE INFLUENCE OF PRODUCT, PRICE, PLACE, PROMOTION, PEOPLE, PROCESS AND PHYSICAL EVIDENCE ON GENERAL PATIENT SATISFACTION IN THE INPATIENT UNIT OF THE ELIM HOSPITAL IN RANTEPAO, NORTH TORAJA REGENCY - Wijaya, Adrian Benedict; Lahindah, Laura (International Journal of Social Service and Research, 2024)
This study aims to analyze the influence of product, price, place, promotion, people, process and physical evidence on general patient satisfaction in the inpatient unit of Elim Rantepao Hospital, North Toraja Regency. The population of this study is 15,798 general patients, of which 375 were taken as samples. The results of the analysis showed that there was a significant influence of the dimensions of Product, Price, Place, Promotion, People, Process, and Physical Evidence on General Patient Satisfaction in the Inpatient Unit of the hospital. The analysis also showed that the 7P Marketing Mix variable of the people dimension had the most influence on patient satisfaction at the hospital with an Exp value (3,395). The chi square p-value test of 0.747 0.05 was used to test the significance value of the dimension of Place on the overall satisfaction of general patients. This study is expected to provide benefits and can provide input from hospitals to improve the quality of hospital services and marketing.